Effect of Hearing Aid Technology Level on New Hearing Aid Users - Hausladen, Jennifer; Plyler, Patrick N.; Clausen, Bailee; Fincher, Ashton; Norris, Sarah; Russell, Teresa (Journal of the American Academy of Audiology, 2022)
Background Hearing aid manufacturers offer several different levels of technology that vary in sophistication and cost. It would stand to reason that higher technology hearing aids would provide greater benefit in the daily life of the user; however, research does not support this assumption for all users. Recent research in experienced hearing aid users indicated noise acceptance and satisfaction for speech in a large group were significantly improved when using the premium devices and suggested noise acceptance may be useful when comparing hearing aid technology levels.Purpose The purpose of this study was to determine the effect of hearing aid technology level on listener outcome measures for new hearing aid users.Research Design A repeated measures, single-blinded research design was utilized.Study Sample Twenty-four adults with no previous hearing aid experience were recruited using flyers posted at the University of Tennessee Audiology Clinic and on social media (19 males, 5 females). The average age of the participants was 61 years (48–81 years).Data Collection and Analysis Participants completed two, 4-week trial periods using Unitron T Moxi Fit FLEX:TRIAL devices programmed with basic or premium technology. Following each trial, laboratory evaluations were conducted using the QuickSIN, Hearing in Noise Test (HINT), and the Acceptable Noise Level (ANL). Subjective data was obtained using the Speech, Spatial, and Qualities of Hearing Short Form, satisfaction ratings, and preference. Data was analyzed using one-way repeated-measures analysis of variance.Results Speech perception results did not reveal significant differences between technology level on the HINT or QuickSIN; however, ANL was significantly improved for the premium devices. Subjective results revealed significantly improved satisfaction for speech in a large group and overall preference when using premium technology.Conclusion Group data revealed similar outcomes between technology levels on most measures; however, noise acceptance, satisfaction for speech in a large group, and overall preference were significantly improved when using the premium devices. Individual characteristics such as noise acceptance, age, and degree of hearing loss may be useful when comparing hearing aid technology levels for new hearing aid users.
Keywords: ANL; hearing aids; sensorineural hearing loss